The History of The Development of Rupiah Currency at The Bank Indonesia Museum - Awaloedin, Dipa Teruna; Pradini, Gagih; Agustiani, Fitri; Bogia, Elvana Jolanda; Raflikeza, M. Firdaus; Ainayya, Lefka (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Currency as a medium of exchange not only has intrinsic value as an economic tool, but also serves as a mirror that reflects the history, culture, and identity of a nation. In the context of Indonesia, the Rupiah currency is not just a sheet of paper or coins but is a legacy that carries the long story of this nation's journey from time to time. Over time, the Rupiah currency has undergone a transformation that includes economic, political, social, and cultural aspects. The rupiah is divided into cents, and its coins and banknotes have various denominations. Bank Indonesia is the monetary authority responsible for the issuance and management of currency in Indonesia. The history of the Indonesian currency reflects the economic development and history of the country throughout time. The collection of artefacts at Museum Bank Indonesia includes a variety of historical objects that reflect economic and financial developments in Indonesia. These include ancient currency, traditional means of payment, banking-related historical documents, as well as other items that have historical value.